Fungal Variation during Peanut Paste Storage - Zamblé Bi Irié Abel Boli; Ollo Kambire; Lessoy Thierry Zoue; Rose Koffi Nevry (International Journal of Microbiology)
Peanut paste produced in multipurpose mills is very often the site of choice for fungal contaminants that pose a major risk to consumers. The objective of this study is to evaluate the level of fungal contamination of peanut paste produced according to different moulding processes during storage. Thirty samples of peanut paste were produced from 60 kg of peanut pods according to three types of moulding (domestic moulding, artisanal moulding, and hygienic moulding) and then preserved for three months. These thirty samples were subjected to microbiological analysis using the conventional mould count method. The moisture content of the various peanut pastes was determined according to the AOAC method. Fungi were identified by using taxonomic schemes based on microscopic observation and culture appearance. Mould loads ranged from 0 to 6.4.102 cfu/g; 91 to 9.6.102 cfu/g; and 0 to 4.6.102 cfu/g, respectively, for domestic, artisanal, and hygienic mouldings during conservation. Moisture content increases during the conservation of peanut paste. It increases from 1.23 to 3.17% for domestic moulding, 1.30 to 3.20% for artisanal moulding, and 1.30 to 2.94% for hygienic moulding. Four fungal genera, namely, Aspergillus, Mucor, Absidia, and Penicillium and three species of Aspergillus including A. flavus, A. fumigatus and A. niger have been identified. The peanut paste produced from domestic and hygienic moulding is less contaminated during storage than that obtained in the artisanal way.